DNA methylation plays important roles in retinal development and diseases. (October 2021) - Wu, Jing; Liu, Lin-lin; Cao, Miao; Hu, Ang; Hu, Die; Luo, Yan; Wang, Hui; Zhong, Jia-ning
Abstract: DNA methylation is important in developing and post-mitotic cells in various tissues. Recent studies have shown that DNA methylation is highly dynamic, and plays important roles during retinal development and aging. In addition, the dynamic regulation of DNA methylation is involved in the occurrence and development of age-related macular degeneration and diabetic retinopathy and shows potential in disease diagnoses and prognoses. This review introduces the epigenetic concepts of DNA methylation and demethylation with an emphasis on their regulatory roles in retinal development and related diseases. Moreover, we propose exciting ideas such as its crosstalk with other epigenetic modifications and retinal regeneration, to provide a potential direction for understanding retinal diseases from the epigenetic perspective. Highlights: DNA methylation is important for regulating developing and post-mitotic cells. It is also involved in age-related macular degeneration and diabetic retinopathy. We reviewed the epigenetic concepts of DNA methylation and demethylation. We emphasized its regulatory roles in retinal development and related diseases.